2011
DOI: 10.1002/gepi.20581
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian semiparametric meta-analysis for genetic association studies

Abstract: We present a Bayesian semiparametric model for the meta-analysis of candidate gene studies with a binary outcome. Such studies often report results from association tests for different, possibly study-specific and non-overlapping genetic markers in the same genetic region. Meta-analyses of the results at each marker in isolation are seldom appropriate as they ignore the correlation that may exist between markers due to linkage disequilibrium (LD) and cannot assess the relative importance of variants at each ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Thus, although there has been previous work on Bayesian methods for meta-analysis (e.g. Sutton and Abrams (2001); Stangl and Berry (2000); DuMouchel and Harris (1983); Whitehead and Whitehead (1991); Li and Begg (1994); Eddy, Hasselblad and Schachter (1990); Givens, Smith and Tweedie (1997); Verzilli et al (2008); De Iorio et al (2011); Burgess et al (2010); Mila and Ngugi (2011)), the nature of our applications calls for a different focus. Specifically our applications need tools for association testing and model comparison, via Bayes Factors (BFs), rather than for estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although there has been previous work on Bayesian methods for meta-analysis (e.g. Sutton and Abrams (2001); Stangl and Berry (2000); DuMouchel and Harris (1983); Whitehead and Whitehead (1991); Li and Begg (1994); Eddy, Hasselblad and Schachter (1990); Givens, Smith and Tweedie (1997); Verzilli et al (2008); De Iorio et al (2011); Burgess et al (2010); Mila and Ngugi (2011)), the nature of our applications calls for a different focus. Specifically our applications need tools for association testing and model comparison, via Bayes Factors (BFs), rather than for estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a method is needed for incorporating LD from an external source into the analysis. Recently, a study showed how LD information from the HapMap or elsewhere could be incorporated into an SNPphenotype association analysis [46].…”
Section: Meta-analysis Assuming Ld Between Snpsmentioning
confidence: 99%
“…αλγορίθμων MCMC. Πρόσφατα, έχει προταθεί μια μπεϋζιανή ημιπαραμετρική προσέγγιση όπου μοντελοποιούνται οι παρατηρηθείσες συχνότητες των γονοτύπων δοθείσης της παρουσίας/απουσίας της νόσου και χρησιμοποιούνται οι εκτιμήσεις της ανισορροπίας σύνδεσης των πολυμορφισμών σαν εκ των προτέρων πληροφορία για την εξαγωγή των εκ των υστέρων εκτιμήσεων (De Iorio,Newcombe et al 2011).από κοινού γονοτύπων, κάτι που σπανίως είναι διαθέσιμο. Έτσι, έχει προταθεί ο υπολογισμός των πιθανοτήτων των από κοινού γονοτύπων με τη χρήση μιας εκτίμησης του βαθμού της ανισορροπίας σύνδεσης υπό τη θεώρηση ότι υπάρχει ισορροπίαHardy-Weinberg.…”
unclassified